PHYSICAL BASIS OF THE FORMATION OF WEATHER AND ANOMALOUS PHENOMENA IN THE NEAR-SURFACE ATMOSPHERE OF THE EARTH - Krasnoboky, Yuriy; Tkachenko, Igor; Ilnitska, Kateryna (Physical and Mathematical Education, 2023)
The article, based on the analysis of modern theories and models, considers the thermodynamic processes that underlie the formation of weather and various anomalous natural phenomena in the Earth’s near-surface atmosphere. Formulation of the problem. Apply the possibilities of the analytical-synthetic approach to explaining the factors that influence the formation of weather and some anomalous atmospheric phenomena, and find out the functional dependencies between the main physical parameters that describe them. Materials and methods. The following research methods were used: analysis of archival meteorological materials; summarizing the data of the annual publications of the UN commissions on climate problems. Results. As a result of the conducted research, it was established that the processes of weather formation and anomalous phenomena in the Earth’s near-surface atmosphere are explained in terms of physical laws that sufficiently describe the state and possible consequences of changes occurring in such open thermodynamic systems as the oceans, land and atmosphere. By varying the real directions and speeds of vertical and horizontal movements of dry and moist air masses under different values of pressure, temperature and density gradients, the conditions for the occurrence of various types of precipitation (rain, hail, snow) and anomalous atmospheric phenomena: thunderstorms, squalls, storms, hurricanes, cyclones, tornadoes, etc. The role of the topography of the relief of the land on the formation of the weather is substantiated. In particular, on both sides of the mountain ridges, the weather is significantly different: going up to the tops of the mountains, the air cools, becomes saturated, and rainy weather forms here; passing over a mountain range, the moisture-depleted air becomes warm, which forms "dry" weather. Conclusions. Based on the received data on the processes of weather formation and anomalous phenomena in the Earth’s near-surface atmosphere, it is possible to draw up an approximate algorithm for its prediction. Thus, if the speed of movement of the center of low pressure in the cyclone is known, it is possible to predict with sufficient accuracy the time when it will reach a certain point located at a distance of 500 km to the east of its real location, as well as the type of weather that will prevail during the approach of this center. In the same way, if the direction of movement of cold or warm fronts of air masses is known, it is possible to predict in advance the type of weather that will prevail in a given area.